PENGARUH ADVERTISING CAMPAIGN, BRAND AMBASSADOR, DAN BRAND AWARENESS TERHADAP MINAT BELI KONSUMEN PADA PRODUK VICTORIA'S SECRET - Millenia Martines (2022)
This research is a quantitative study aimed at knowing the effect of advertising campaigns, brand ambassadors, and brand awareness on consumer purchase intention in Victoria's Secret products. The population in this research is women who live in DKI Jakarta. The sampling technique used is a non-probability sampling technique with purposive sampling. The data was obtained by distributing questionnaires to 105 respondents. The analytical tools used are descriptive statistics and multiple linear regression analysis which are processed using SPSS version 27. The results show that advertising campaigns have no effect on buying interest in Victoria's Secret products. Brand ambassadors have an effect on buying interest in Victoria's Secret products. Brand awareness has a partial effect on buying interest in Victoria's Secret products. Keywords: Advertising Campaign, Brand Ambassador, Brand Awareness, Purchase Intention